2016
DOI: 10.1155/2016/2919034
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Regulation Effects of Raw and Processed Notoginseng Radix Et Rhizome on Steatotic Hepatocyte L02 Cell

Abstract: Introduction. Raw and processed Notoginseng Radix Et Rhizome (NRR) have been widely used in treatment of metabolic syndromes and related disease, including nonalcoholic fatty liver disease (NAFLD). This study was designed to investigate lipid regulation effects of raw and processed NRR in steatotic L02 cell. Materials and Methods. Steatotic L02 cells were obtained after being cultured with 5% fat emulsion-10% FBS-RPMI 1640 medium for 48 h. Contents of total cholesterol (TC), triglyceride (TG), free fatty acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…Lau et al [9] compared the bleeding time (BT) in rats orally treated with raw and steamed PN roots and found that the treatment with raw PN extract resulted in shorter BT compared with rats treated with the steamed PN extract. Besides, raw PN extract displayed a much better lipid-lowering effect than steamed PN by investigating the levels of total cholesterol and triglyceride in steatotic L02 cells [10]. Such difference might be attributed to the change in the contents, relative proportion, and structures of chemical constituents in PN.…”
Section: Introductionmentioning
confidence: 97%
“…Lau et al [9] compared the bleeding time (BT) in rats orally treated with raw and steamed PN roots and found that the treatment with raw PN extract resulted in shorter BT compared with rats treated with the steamed PN extract. Besides, raw PN extract displayed a much better lipid-lowering effect than steamed PN by investigating the levels of total cholesterol and triglyceride in steatotic L02 cells [10]. Such difference might be attributed to the change in the contents, relative proportion, and structures of chemical constituents in PN.…”
Section: Introductionmentioning
confidence: 97%
“…LC-QQQ-MS/MS analysis revealed that isoquercitrin, typhaneoside, isorhamnetin-3-O-neohesperidoside, and notoginsenoside R1 were the chemical components with high contents in these extracts. In addition, previous in vivo and in vitro studies have found that alisol B 23-acetate, alisol A 24-acetate, nuciferine, rutin, isoquercitrin, quercetin, isorhamnetin, and notoginsenoside R1 were effective in protecting against hepatic steatosis [ 23 29 ]. Therefore, these compounds may be identified as potential chemical markers, which may provide a chemical basis for the study of Q-markers in HGQZ.…”
Section: Discussionmentioning
confidence: 99%
“…GRb1 isolated from ginseng, another traditional Chinese medicine, has been proven to have therapeutic effects on treating obesity and diabetes [ 19 21 ]. Additionally, GRb1 is involved in IR via 11beta-hydroxysteroid dehydrogenase type I in our previous study [ 22 ] and NAFLD in other's study [ 23 ]. Moreover, GRb1 showed the ability to activate PPAR- γ [ 24 ] and be involved in the regulation of IR [ 25 ].…”
Section: Introductionmentioning
confidence: 92%